Experimental and Numerical Assessment of the Multi-physics Dynamic Response for a MEMS Accelerometer at Various Gaps. (2016) - Ardito, Raffaele; De Masi, Biagio; Cerini, Fabrizio; Ferrari, Marco; Ferrari, Vittorio; Russo, Alfio; Urquia, Mikel Azpeitia; Sedmik, René I.P.
Abstract: The dynamic response of a MEMS accelerometer can be influenced by several multi-physics effects, especially if the gaps between the shuttle and the stator attain sub-micrometric values. The present paper aims at tackling the aforementioned issues by means of a suitable experimental procedure, which has been purposely devised for the problem at hand, and through the execution of numerical analyses (based on the Finite Element Model). The effect of parasitic electrostatic forces and hydrodynamic forces is clearly demonstrated.